2010
DOI: 10.1007/s11916-009-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Headaches and the Neurobiology of Somatization

Abstract: Pain sensitivity is an adaptive process affected by expectation, mood, coping, operant conditioning, and the preconscious allocation of attention. Underlying mechanisms may include encoding of similar experiences (eg, depression, loss, pain-distress) in overlapping patterns of activation, failure of common regulatory mechanisms, direct top-down activation of the pain matrix, and changes in descending pain facilitatory and inhibitory tone. In theory, the combination of glial cell activation from psychological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…We discarded the first 3 images of each run to allow for equilibration of the longitudinal magnetization. The preprocessing steps included 1. the realignment and unwarping of the images to correct for movement artifacts and related susceptibility artifacts, 2. a coregistration of the anatomic to the functional images, 3. the segmentation and normalization of the anatomic image to the standard stereotactic space (Montreal Neurological Institute [MNI]), 4 4. the application of a normalization transformation to the functional images, and 5. the smoothing with a 8 mm Gaussian kernel for the group analysis.…”
Section: Image Processing and Data Analysis: Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…We discarded the first 3 images of each run to allow for equilibration of the longitudinal magnetization. The preprocessing steps included 1. the realignment and unwarping of the images to correct for movement artifacts and related susceptibility artifacts, 2. a coregistration of the anatomic to the functional images, 3. the segmentation and normalization of the anatomic image to the standard stereotactic space (Montreal Neurological Institute [MNI]), 4 4. the application of a normalization transformation to the functional images, and 5. the smoothing with a 8 mm Gaussian kernel for the group analysis.…”
Section: Image Processing and Data Analysis: Preprocessingmentioning
confidence: 99%
“…1 Although the causes and mechanisms behind this mental disorder remain unclear, both functional and structural alterations in the limbic structures seem to correlate with this non-nociceptive chronic pain condition. [2][3][4] Moreover, human brain imaging studies have revealed new roles that cortical neuronal networks play in chronic pain, 5 including the unpleasant quality of pain. 6 The current study expanded upon a new approach for testing one important facet of the network model to examine the intrinsic functional connectivity between networks active during resting state: the functional network connectivity (FNC).…”
Section: Introductionmentioning
confidence: 99%
“…Providers are often untrained and unmotivated to diagnose and treat headache patients [4,5,6,7,8,9,10] and many have an inappropriate perception of the burden of headache disorders [4,11] or consider headaches a somatoform disorder [12,13,14]. This results in misdiagnosis [6,11,15] and ineffective treatment [6,7,11], which increases patient dissatisfaction and insecurity [15] with consequent doctor ‘shopping', unnecessary testing and inadequate self-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Such results may be explained by the results of a study asserting that continuous stress neuro-physiologically affected the brain, changing pain sensibility leading to physical manifestation and chronic headache, and the outcome of a study reporting that incessant stress was associated with digestive disorders, such as irritable bowel syndrome in the group with immense stress and high score of physical symptoms 10,11). Furthermore, chronic fatigue syndrome is associated with irritable bowel syndrome and fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%